Multilevel Analysis: The Effect of Socioeconomic, Birth Weight, and Nutrition Intake with Wasting in Boyolali, Central Java - Roobiati, Nur Fika; Poncorini, Eti; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Wasting is a major health problem. Globally, wasting accounts for 4.7% of all deaths of children aged under 5 years. Severely wasted children are, on average, 11 times more likely to die than their healthy counterparts. This study aimed to investigate the effect of socioeconomic, birth weight, and nutrition intake with wasting in Boyolali, Central Java, using multilevel analysis. Subjects and Method: This was an analytic observational study with a case control design. The study was conducted in Boyolali, Central Java, from April to May 2018. Twenty five posyandus (integrated health posts) were selected and positioned at level 2 in the multilevel model (MLM) analysis. A sample of 200 children under five was selected for this study by fixed disease sampling and positioned at level 1 in the MLM. The dependent variable was wasting. The independent variables were birth weight, nutrition intake, maternal education, family income, and family size. Data on wasting was measured by microtoise and weight scale. Nutrition intake was measured by food recall. The other variables were collected by questionnaire. Data were analyzed by a MLM analysis. Results: The risk of wasting decreased with high family income (b= -1.92; 95% CI= -3.77 to -0.08; p= 0.041), high maternal education (b= -2.68; 95% CI= -4.97 to -0.38; p= 0.022), small family size (b= -2.01; 95% CI= -3.67 to -0.35; p= 0.018), normal birth weight (b= -2.55; 95% CI= -4.89 to -0.21; p= 0.033), good nutritional intake (b= -2.18; 95% CI= -3.95 to -0.41; p= 0.016). Posyandu had a contextual effect on wasting with ICC= 21.45%. Conclusion: The risk of wasting decreases with high family income, high maternal education, small family size, normal birth weight, good nutritional intake. Posyandu has a contextual effect on wasting. Keywords: wasting, socioeconomic, birth weight, nutrition intake, children under five Correspondence: